Pengembangan Instrumen Tes untuk Mengukur Hasil Belajar Materi Pecahan Siswa Kelas IV SD - Sherli Fitri Veronica; Viktor Pandra; Elya Rosalina (Journal of Elementary School (JOES), 2023)
The purpose of this study was to find out how to make a test instrument that is valid and reliable and able to help measure the learning outcomes of fourth grade students in fractional material, especially at Elementary School in Lubuklinggau City. The model used is a modification of the Wilson model and the Oriondo and Antonio models which have been adopted in the process of preparing the learning achievement test, along with the stages that must be passed in preparing the test instrument, including: 1) Initial development of the test; 2) Trial test; and 3) Implementation of test measurements. The implementation results obtained show that this test instrument is able to measure student learning outcomes with an average percentage of students obtaining a score of 53.81% with those obtaining a score that meets the KKM of 51% and those that do not fulfill it by 49%. Based on the data obtained by researchers, it shows that the development of test instruments to measure learning outcomes, especially fraction material, must have good validity and reliability. Keywords: Test Instruments, Learning Outcomes, Fractions